Multifunctional composite filler modified water-based paint and preparation method thereof
By using modified calcium-aluminum hydrotalcite materials, grafted modified graphene/boron nitride materials and functionalized carbon black multifunctional composite fillers in automotive coatings, the problems of insufficient functionality and poor compatibility of existing fillers are solved. , achieving a significant improvement in coating performance.
Patent Information
- Application Number
- CN202510079424.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-18
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-18
AI Technical Summary
The existing automotive coating fillers are ineffective and have poor compatibility with the coating matrix, which affects the performance of the coating.
The multifunctional composite filler is used, including a mixture of modified calcium-aluminum hydrotalcite, grafted modified graphene/boron nitride material and functional carbon black, and its compatibility with the coating matrix is improved by the modification treatment.
It significantly improves the comprehensive performance of water-based coatings, including flame retardant properties, impact resistance, antibacterial properties and chemical resistance, and is simple to operate and suitable for industrial production.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a water-based coating modified with a multifunctional composite filler and a preparation method thereof. Background Art
[0002] With the rapid development of the automobile industry, the rapid development of automobile coatings has also been driven. Automobile coatings represent the highest technical level and development direction of the coatings industry. Automobile coatings play a vital role in automobile manufacturing and maintenance. They not only provide beautiful appearance for the car, but also have a variety of practical functions. For example, automobile coatings can effectively isolate the car body from direct contact with air, moisture and corrosive substances, thereby preventing the car body from rusting and corrosion, which is crucial to extending the service life of the car; high-quality automobile coatings can also resist harsh environmental factors such as ultraviolet rays, high temperature, humidity, etc., to maintain the beauty and performance of the car body.
[0003] Automotive coatings include water-based automotive coatings and solvent-based automotive coatings. Traditional automotive coatings are mostly solvent-based coatings, which emit a large amount of VOCs during use. In order to meet environmental protection requirements, water-based automotive coatings have been more widely developed. With the development of automotive coatings, the functional requirements for automotive coatings are becoming higher and higher. For example, water-based automotive topcoats require high gloss, high image clarity, high weather resistance, scratch resistance, and acid rain resistance. At present, the functional improvement of automotive coatings is mainly to add fillers. At present, the following problems exist when using fillers to modify automotive coatings: First, the fillers used are not functional enough and cannot improve the performance of automotive coatings well; Second, the compatibility of fillers with the automotive coating matrix is not good during modification, and they are easy to agglomerate in the matrix, which will affect the performance of the coating. Therefore, how to provide a filler that has good compatibility with the coating matrix and excellent functionality is the key to improving automotive coatings. Summary of the invention
[0004] One of the technical problems to be solved by the present invention is: in view of the deficiencies in the prior art, a water-based paint modified with a multifunctional composite filler is provided. The water-based paint is modified by adding an appropriate amount of the multifunctional composite filler and has excellent performance and good stability.
[0005] The second technical problem to be solved by the present invention is to provide a method for preparing a water-based coating modified with a multifunctional composite filler, which optimizes various process conditions so that the components in the water-based coating have good compatibility. The prepared coating has not only good stability and excellent performance, but also the preparation method is simple to operate and is suitable for industrial production.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: In a first aspect, the present invention provides a water-based coating modified with a multifunctional composite filler, which comprises, by weight, 80-100 parts of a modified core-shell acrylic dispersion, 5-7 parts of a multifunctional composite filler, 0.5-1 parts of a defoamer, 0.5-1 parts of a wetting agent, 2-5 parts of a thickener, 1-2 parts of a film-forming aid, and 25-35 parts of deionized water; the multifunctional composite filler is a mixture of a modified calcium aluminum hydrotalcite material, a grafted modified graphene / boron nitride material, and functionalized carbon black, and the mass ratio of the modified calcium aluminum hydrotalcite material, the grafted modified graphene / boron nitride material, and the functionalized carbon black is (2-5): (3-8): (10-20); the core of the modified core-shell acrylic dispersion is nano-titanium dioxide, and the outer layer is coated with acrylic resin and fluorine-modified acrylic resin in sequence; The modified calcium aluminum hydrotalcite material is prepared by first inserting sodium dodecylbenzene sulfonate between the calcium aluminum hydrotalcite material layers, and then inserting acrylamide; The grafted modified graphene / boron nitride material is prepared by silanization treatment after intercalation of graphene and boron nitride, and finally graft polymerization modification with methacryloyloxyethyl sulfobetaine as a monomer; The functionalized carbon black is prepared by pre-treating carbon black and then modifying it with beta-cyclodextrin and glycerol phytate ammonium salt. The glycerol phytate ammonium salt is prepared by esterifying glycerol with phytate and then reacting with urea for complexation.
[0007] Preferably, the preparation method of the modified calcium aluminum hydrotalcite material specifically comprises the following steps: Calcium aluminum hydrotalcite is dispersed in deionized water to obtain a calcium aluminum hydrotalcite dispersion, sodium dodecylbenzene sulfonate solution is added to the calcium aluminum hydrotalcite dispersion, acrylamide solution is added after ultrasonic dispersion treatment, and the pH of the solution is adjusted to react. After the reaction is completed, the reaction solution is cooled to room temperature, the reaction solution is filtered, the precipitate is washed, and then dried to obtain a modified calcium aluminum hydrotalcite material.
[0008] Calcium aluminum hydrotalcite has excellent heat resistance and flame retardant properties, and has a layered structure. In order to improve its compatibility with the coating matrix, it needs to be modified. However, the interlayer spacing of calcium aluminum hydrotalcite is small, and it is difficult to modify the modified material on its surface and between layers. In order to solve the above problems, the present invention is based on the ion exchange characteristics of calcium aluminum hydrotalcite, firstly inserts sodium dodecylbenzene sulfonate between the calcium aluminum hydrotalcite layers through ion exchange to expand its interlayer spacing, and then exchanges acrylamide macromolecules into the intercalation, thereby preparing an organic-inorganic hybrid material, and due to the similar miscibility principle between the interlayer acrylamide of the organic-inorganic hybrid material and the coating matrix, it can be evenly dispersed in the coating matrix.
[0009] Preferably, the concentrations of the calcium aluminum hydrotalcite dispersion, sodium dodecylbenzene sulfonate solution, and acrylamide solution are 0.05-0.08 g / ml, 0.05-0.06 g / ml, and 0.02-0.05 g / ml, respectively; the mass ratio of the calcium aluminum hydrotalcite dispersion, sodium dodecylbenzene sulfonate solution, and acrylamide solution is 1:1:(0.5-1).
[0010] Preferably, the reaction pH is 3.5-4.5, the temperature is 80° C., and the reaction time is 3-5 h.
[0011] Preferably, the preparation method of the grafted modified graphene / boron nitride material comprises the following steps: Graphene and boron nitride are added to anhydrous ethanol, ultrasonically treated, and then filtered. The precipitate is directly added to a methacrylate-3-(trimethoxysilyl)propyl ester solution without drying for immersion activation treatment, and then filtered. The precipitate is washed and directly added to a mixed solution of methacryloyloxyethyl sulfobetaine, a photoinitiator, and N,N-methylenebisacrylamide without drying. After stirring and dispersing evenly, ultraviolet graft polymerization is carried out. Finally, the reaction solution is filtered, the precipitate is washed and dried to obtain a grafted modified graphene / boron nitride composite material.
[0012] Boron nitride nanosheets and graphene both have high thermal stability and chemical stability, good mechanical properties and flexibility, and have certain absorption and scattering effects on ultraviolet light. The nanosheet structure of the two can destroy the cell walls and cell membranes of bacteria, thereby killing or inhibiting the growth of bacteria. Adding boron nitride nanosheets and graphene to the coating matrix can effectively improve the comprehensive performance of the coating.
[0013] In order to improve the compatibility of boron nitride nanosheets, graphene and a coating matrix, the present invention firstly performs mixed ultrasonic treatment on graphene and boron nitride, and utilizes the cavitation effect and shear force generated by the ultrasonic treatment to effectively break the agglomeration between nanomaterials, thereby improving the dispersibility of graphene and boron nitride nanosheets; in order to avoid the dispersed nanomaterials from forming hard agglomerates, the precipitate is directly added to a methacrylate-3-(trimethoxysilyl)propyl ester solution without drying for immersion activation treatment, and methacrylate-3-(trimethoxysilyl)propyl ester can form chemical bonds with functional groups on the surfaces of graphene and boron nitride, thereby further improving its dispersibility and compatibility with the coating matrix, and facilitating the next step of processing of graphene and boron nitride nanosheets. In order to further improve the dispersibility of graphene and boron nitride nanosheets, the present invention also uses methacryloyloxyethyl sulfobetaine as a grafting monomer for grafting modification. The polymer chains generated by the polymerization reaction will entangle or coat the surfaces of the graphene and boron nitride nanomaterials. On the one hand, their compatibility with the coating matrix is further improved; on the other hand, the polymer layer can combine with the bacterial cell membrane through electrostatic action, change the permeability of the cell membrane, and thus inhibit the growth of bacteria.
[0014] Preferably, the mass ratio of graphene to boron nitride is (2-5):1; the power of ultrasonic treatment is 200-500W, and the ultrasonic time is 1-3h.
[0015] Preferably, the 3-(trimethoxysilyl)propyl methacrylate solution is prepared by adding 3-(trimethoxysilyl)propyl methacrylate to a mixed solution of methanol and deionized water; the volume ratio of 3-(trimethoxysilyl)propyl methacrylate, methanol and deionized water is 5:(90-95):(3-5).
[0016] Preferably, the temperature of the immersion activation treatment is room temperature, the time is 20-30 hours, and the mass ratio of the precipitate to 3-(trimethoxysilyl)propyl methacrylate is 1:(0.03-0.05).
[0017] Preferably, during the ultraviolet graft polymerization, the mass ratio of the precipitate to the methacryloyloxyethyl sulfobetaine is 1:(0.01-0.05).
[0018] Preferably, the photoinitiator is 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, and in the mixed solution, deionized water is used as the solvent, the concentration of methacryloxyethyl sulfobetaine is 0.1-0.2 g / ml, and the mass ratio of methacryloxyethyl sulfobetaine, methylenebisacrylamide, and photoinitiator is 5: (0.02-0.03): (0.01-0.05).
[0019] Preferably, the conditions for ultraviolet graft polymerization are: irradiation with a high-pressure mercury lamp with a power of 400 W and an ultraviolet wavelength of 365 nm, a radiation distance of 15 cm, and a time of 20-30 min.
[0020] Preferably, the method for preparing the functionalized carbon black comprises the following steps: Phytic acid and glycerol are added to ethanol to carry out a temperature reaction, and then urea is added to the reaction system to carry out a second temperature reaction. After the reaction is completed, it is cooled to room temperature, β-cyclodextrin and pretreated carbon black are added to the reaction system, ultrasonic treatment is carried out, and finally the reaction solution is filtered, the precipitate is washed and dried to obtain functionalized carbon black.
[0021] Carbon black is a carbonaceous material with excellent performance. It has excellent UV resistance and can be added to coatings as a reinforcing filler to improve the performance of the coating. However, it has poor compatibility with the coating matrix, and directly adding it to the coating will reduce the performance of the coating. In order to solve the above technical problems, the present invention first esterifies phytic acid and glycerol under certain conditions, and then performs a complex reaction with urea to obtain phytic acid glycerol ammonium salt, which is modified on the surface of pretreated carbon black, which can not only improve the compatibility of carbon black with the coating matrix, but also the phosphorus-containing phytic acid glycerol ammonium salt and carbon black have flame retardant effects, thereby improving the performance of the coating.
[0022] Preferably, the molar ratio of phytic acid, glycerol and urea is (0.02-0.03):(0.09-0.1):(0.1-0.2).
[0023] Preferably, the mass ratio of β-cyclodextrin, pretreated carbon black and phytic acid is 2:1:(0.5-1).
[0024] Preferably, the temperature of the first temperature-raising reaction is 130° C. and the time is 2-3 h; the temperature of the second temperature-raising reaction is 110° C. and the time is 2-3 h.
[0025] Preferably, the temperature of the ultrasonic treatment is room temperature, the power is 200-500 W, and the time is 20-50 min.
[0026] In a second aspect, the present invention provides a method for preparing a water-based coating modified with a multifunctional composite filler, comprising the following steps: (1) preparing an emulsifier solution, stirring and mixing the first monomer and the emulsifier solution to obtain a first pre-emulsion; adding the fluorine-containing second monomer to the emulsifier solution, stirring and mixing to obtain a second pre-emulsion; (2) Add nano titanium dioxide to the emulsifier solution, stir evenly to obtain a dispersion, add 1 / 3 of the first pre-emulsion to the dispersion, heat it to 80±2°C, add 1 / 3 of the initiator solution, react until blue light appears, add the remaining first pre-emulsion and initiator solution, continue to heat to 87±2°C after the addition is completed, and keep the reaction warm for 0.5-1h; (3) After the reaction is completed, the reaction system is cooled to 80±2°C, and the second pre-emulsion and the initiator solution are added to the reaction solution. After the addition is completed, the temperature is raised to 87±2°C and the temperature is kept to react for 0.5-1h. After the reaction is completed, the reaction solution is cooled to room temperature to obtain a modified core-shell acrylic dispersion; (4) The modified core-shell acrylic dispersion, multifunctional composite filler, defoamer, wetting agent, thickener, film-forming aid and deionized water are mixed and dispersed uniformly according to the measured ratio to obtain a water-based coating.
[0027] Preferably, the emulsifier solution is a sodium dodecyl sulfate solution with a concentration of 0.5-1 wt%.
[0028] Preferably, in step (1), the first monomer is a mixture of methyl methacrylate, butyl acrylate and acrylic acid, and when preparing the first pre-emulsion, the mass ratio of methyl methacrylate, butyl acrylate, acrylic acid and sodium dodecyl sulfate is (8-15): (10-15): 3: (0.3-0.5); and / or the fluorine-containing second monomer is a mixture of methyl methacrylate, butyl acrylate, acrylic acid, glycidyl methacrylate, isooctyl acrylate, hydroxyethyl methacrylate, and trifluoroethyl acrylate. When preparing the second pre-emulsion, the mass ratio of methyl methacrylate, butyl acrylate, acrylic acid, glycidyl methacrylate, isooctyl acrylate, hydroxyethyl methacrylate, trifluoroethyl acrylate, and sodium dodecyl sulfate is (5-8): (10-12): (1-2): (2-4): (1-1.5): (2-4): (2-3): (0.3-0.5); During the polymerization, the volume ratio of the first pre-emulsion, the second pre-emulsion and the emulsifier solution in the dispersion is 3:3:10.
[0029] Preferably, in step (2), the mass ratio of nano titanium dioxide to emulsifier is 5:(1-1.5).
[0030] Preferably, the initiator solution is a potassium persulfate solution with a concentration of 1 wt %. In step (2), the mass ratio of the initiator solution to the emulsifier solution in the dispersion is 1:(4-5). In step (3), the amount of the initiator solution added is 0.2-0.3 times the mass of the emulsifier solution in the dispersion.
[0031] Due to the adoption of the above technical solution, the present invention has at least the following beneficial effects: 1. The present invention provides a water-based paint modified with a multifunctional composite filler, comprising a modified core-shell acrylic dispersion, a multifunctional composite filler, a defoamer, a wetting agent, a thickener, a film-forming aid, and deionized water; the core of the modified core-shell acrylic dispersion is nano-titanium dioxide, and the outer layer is coated with acrylic resin and fluorine-modified acrylic resin in sequence; a certain amount of nano-titanium dioxide is added when preparing the emulsion, and the nano-titanium dioxide can absorb ultraviolet rays, reflect and scatter ultraviolet rays, and has good chemical stability, and can improve the chemical reagent resistance and ultraviolet resistance of the paint to a certain extent; and the shell material fluorine-modified acrylic resin has excellent weather resistance and wear resistance; the special structure of the modified core-shell acrylic dispersion enables the nano-titanium dioxide to be effectively coated in the acrylic resin and the fluorine-modified acrylic resin, thereby avoiding the agglomeration of nanoparticles; the present invention also modifies the paint by a self-made multifunctional composite filler, and the obtained water-based paint has good comprehensive performance.
[0032] 2. The multifunctional composite filler of the present invention comprises a certain amount of modified calcium aluminum hydrotalcite material, which is firstly prepared by inserting sodium dodecylbenzene sulfonate between the calcium aluminum hydrotalcite material layers and then inserting acrylamide. The modified calcium aluminum hydrotalcite material has good interface properties with the coating matrix. The calcium aluminum hydrotalcite material has certain flame retardant properties. During the combustion process, interlayer dehydration and dehydroxylation reactions will occur, releasing water and carbon dioxide, which can dilute and block combustible gases. Moreover, the residue after decomposition is a mixed metal oxide, which can effectively absorb harmful gases and promote the formation of dense carbon slag, has the dual effects of flame retardancy and smoke suppression, and can effectively improve the flame retardant properties of the coating. Moreover, the modified calcium aluminum hydrotalcite material has a large specific surface area and excellent dispersibility, and can form a close combination with the coating matrix, thereby improving the mechanical properties and impact resistance of the coating.
[0033] 3. The multifunctional composite filler of the present invention includes a certain amount of grafted modified graphene / boron nitride material. First, graphene and boron nitride are subjected to ultrasonic composite treatment, then silanization treatment, and finally methacryloyloxyethyl sulfobetaine is used as a monomer for graft polymerization modification, thereby forming a polymer coating on the surface of the graphene / boron nitride material, thereby improving the compatibility of the graphene / boron nitride material with the coating matrix. Graphene and boron nitride are two-dimensional layered materials with excellent performance. Graphene and boron nitride have good thermal stability and excellent barrier properties, and can improve the limiting oxygen index of the coating at high temperatures. The sheet structure of graphene and boron nitride can also disperse the impact force well, so that the coating can better absorb and disperse energy when impacted, thereby improving the impact resistance of the coating, and can also significantly improve the tensile strength of the coating. In addition, graphene and boron nitride themselves have a certain absorption and scattering effect on ultraviolet light, and their nanosheet structure can destroy the cell wall and cell membrane of bacteria, thereby killing or inhibiting the growth of bacteria, thereby improving the UV resistance and antibacterial properties of the coating.
[0034] 4. The multifunctional composite filler of the present invention includes a certain amount of functionalized carbon black. First, the carbon black is pretreated and active groups are introduced on the surface of the carbon black to facilitate the subsequent modification of the carbon black. The modified materials β-cyclodextrin and glycerol phytate ammonium salt have multiple active groups such as hydroxyl and carboxyl groups, which can react with the active groups on the surface of carbon black to form strong chemical bonds. β-cyclodextrin can be used as a dispersant, stabilizer or thickener in the coating to improve the dispersibility, stability and fluidity of the coating, while glycerol phytate ammonium salt can also interact with other components in the coating to improve the adhesion, hardness and chemical resistance of the coating. In addition, the introduction of β-cyclodextrin and glycerol phytate ammonium salt can significantly improve the dispersibility and stability of carbon black in the coating, help reduce the agglomeration and precipitation of carbon black, and make the coating more uniform and delicate.
[0035] 5. The present invention adopts modified calcium aluminum hydrotalcite material, grafted modified graphene / boron nitride material and functionalized carbon black compound as multifunctional fillers to modify the coating. The surfaces of modified calcium aluminum hydrotalcite material and grafted modified graphene / boron nitride material have abundant active groups. The interlayer structure of modified calcium aluminum hydrotalcite can provide a large surface area, which provides a good basis for the dispersion and interaction of other materials. The grafted modified graphene / boron nitride material can interact with the surface of calcium aluminum hydrotalcite while providing high electrical conductivity and thermal conductivity, thereby improving the material The overall performance of the water-based coating can be improved by modifying calcium aluminum hydrotalcite, improving the mechanical properties, corrosion resistance and flame retardancy of the coating, while grafted modified graphene can help improve the conductivity and thermal stability of the coating, and functionalized carbon black can enhance the hiding power and wear resistance of the coating. The superposition of the above excellent effects can significantly improve the comprehensive performance of the coating; the modified calcium aluminum hydrotalcite, graphene and boron nitride can enhance the compatibility with the coating matrix through surface chemical modification, and the improvement of the compatibility between the components is conducive to the good adhesion between the materials, thereby improving the adhesion, wear resistance and anti-aging ability of the coating. In summary, the good combination of modified calcium aluminum hydrotalcite, grafted modified graphene / boron nitride and functionalized carbon black, which work together, greatly improves the comprehensive performance of water-based coatings. DETAILED DESCRIPTION
[0036] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0037] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.
[0038] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0039] In the following examples and comparative examples, the performance parameters and sources of some raw materials are as follows: The defoamer is BYK-028, the wetting agent is BYK-346, the film-forming aid is alcohol ester-12, and the thickener is Alesun RM-12W; Calcium aluminum hydrotalcite: Hubei Tosoh Chemical Technology Co., Ltd.; Graphene: Carboxylated graphene oxide powder purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with a flake diameter of 0.5-5 μm and a thickness of 0.8-1.2 nm; Boron nitride: hydroxylated boron nitride nanosheets purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; Nano titanium dioxide: TiO2 anatase nano titanium dioxide, with an average particle size of 30-40 nm, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; Carbon black: Environmentally friendly carbon black N550, Qingzhou Bio Carbon Black Co., Ltd.; The process of carbon black pretreatment is as follows: 2g of carbon black and 20ml of 60wt% nitric acid solution are ultrasonically dispersed at 300W for 30min, heated to 100°C under an inert atmosphere for 24h, filtered after the treatment, and the precipitate is washed to neutrality and then dried to obtain pretreated carbon black.
[0040] Unless otherwise specified, all raw materials of the present invention are commercially available or available to those skilled in the art. Unless otherwise specified, all methods of the embodiments of the present invention are methods known to those skilled in the art. Example 1
[0041] The preparation method of the multifunctional composite filler comprises the following steps: S1: 7g of calcium aluminum hydrotalcite was dispersed in 100ml of deionized water to obtain a calcium aluminum hydrotalcite dispersion, and a sodium dodecylbenzene sulfonate solution prepared by mixing 5g of sodium dodecylbenzene sulfonate with 100ml of deionized water was added to the calcium aluminum hydrotalcite dispersion. After ultrasonic dispersion treatment at 500W for 10min, an acrylamide solution prepared by mixing 60ml of deionized water with 3g of acrylamide was added. The pH of the solution was adjusted to 4, and the temperature was raised to 80°C for reaction for 4h. After the reaction was completed, the reaction solution was cooled to room temperature, the reaction solution was filtered, the precipitate was washed, and then dried to obtain a modified calcium aluminum hydrotalcite material; S2: 3 g of graphene and 1 g of boron nitride were added to 50 ml of anhydrous ethanol, and ultrasonically treated at 500 W for 3 h. The precipitate was then filtered and added directly to a 3-(trimethoxysilyl)propyl methacrylate solution (a solution composed of 3-(trimethoxysilyl)propyl methacrylate, methanol, and deionized water in a volume ratio of 5:95:4) without drying. The precipitate was immersed and activated at room temperature for 24 h. During the immersion and activation treatment, the mass ratio of the precipitate to 3-(trimethoxysilyl)propyl methacrylate was 1:0.03. After the immersion and activation treatment, the precipitate was filtered, and the precipitate was washed and added directly to methacryloyloxyethyl sulfobetaine, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, N,N- In a mixed solution of methylbisacrylamide (in the mixed solution, the mass ratio of methacryloyloxyethyl sulfobetaine, methylenebisacrylamide, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone and deionized water is 5:0.02:0.02:45), the mass ratio of precipitate to methacryloyloxyethyl sulfobetaine is controlled to be 1:0.04, after stirring and dispersing at a speed of 1000 rpm for 30 minutes, the reaction solution is irradiated with a high-pressure mercury lamp with a power of 400 W and a wavelength of ultraviolet light of 365 nm, the distance between the high-pressure mercury lamp and the surface of the reaction solution is controlled to be 15 cm, the time is 30 minutes, after the reaction is completed, the reaction solution is filtered, the precipitate is washed and dried, and a grafted modified graphene / boron nitride composite material is obtained; S3: Add 0.025 mol phytic acid and 0.09 mol glycerol to 50 ml ethanol, heat to 130°C, react for 3 hours, cool the reaction solution to 110°C, then add 0.11 mol urea to the reaction system, keep warm for 2 hours, cool to room temperature after the reaction, add β-cyclodextrin and pretreated carbon black to the reaction system (control the mass ratio of β-cyclodextrin, pretreated carbon black, and phytic acid to be 2:1:0.5), ultrasonically treat at 500W for 30 minutes, and finally filter the reaction solution, wash the precipitate, and dry to obtain functionalized carbon black; S4: Mix and grind the mixture of the modified calcium aluminum hydrotalcite material, the grafted modified graphene / boron nitride material, and the functionalized carbon black in a mass ratio of 3:4:15 to obtain a multifunctional composite filler. Example 2
[0042] Compared with Example 1, the difference is that in S4, the ratio of the mixture of modified calcium aluminum hydrotalcite material, grafted modified graphene / boron nitride material and functionalized carbon black is 3:5:20, and other conditions are the same as in Example 1.
[0043] Comparative Example 1 Compared with Example 1, the difference is that the filler only includes modified calcium aluminum hydrotalcite material, and other conditions are the same as those in Example 1.
[0044] Comparative Example 2 Compared with Example 1, the difference is that the filler only includes grafted modified graphene / boron nitride material, and other conditions are the same as Example 1.
[0045] Comparative Example 3 Compared with Example 1, the difference is that the filler only includes functionalized carbon black, and other conditions are the same as those in Example 1.
[0046] Comparative Example 4 Compared with Example 1, the difference is that the filler does not include modified calcium aluminum hydrotalcite material, and other conditions are the same as those in Example 1.
[0047] Comparative Example 5 Compared with Example 1, the difference is that the filler does not include grafted modified graphene / boron nitride material, and other conditions are the same as Example 1.
[0048] Comparative Example 6 Compared with Example 1, the difference is that the filler does not include functionalized carbon black, and other conditions are the same as those in Example 1. Example 3
[0049] A method for preparing a water-based coating modified with a multifunctional composite filler comprises the following steps: (1) 0.5 g of sodium dodecyl sulfate and 100 ml of deionized water are mixed and stirred to obtain a sodium dodecyl sulfate solution, methyl methacrylate, butyl acrylate, acrylic acid and sodium dodecyl sulfate solution are mixed and stirred evenly (the mass ratio of methyl methacrylate, butyl acrylate, acrylic acid and sodium dodecyl sulfate is controlled to be 8:10:3:0.4), and the mixture is stirred evenly to obtain a first pre-emulsion; methyl methacrylate, butyl acrylate, acrylic acid, glycidyl methacrylate, isooctyl acrylate, hydroxyethyl methacrylate, trifluoroethyl acrylate and sodium dodecyl sulfate solution are mixed and stirred evenly (the mass ratio of methyl methacrylate, butyl acrylate, acrylic acid, glycidyl methacrylate, isooctyl acrylate, hydroxyethyl methacrylate, trifluoroethyl acrylate and sodium dodecyl sulfate is controlled to be 7.5:10:1.2:3:1.2:3:3:0.35) to obtain a second pre-emulsion; (2) Add nano titanium dioxide (the mass ratio of nano titanium dioxide to sodium dodecyl sulfate is 5:1) to 50 ml of 0.5 wt% sodium dodecyl sulfate solution, stir evenly, add 5 ml of the first pre-emulsion, heat to 80 °C, add 3.3 g of 1 wt% potassium persulfate solution, react until blue light appears, add 10 ml of the first pre-emulsion and 6.7 g of potassium persulfate solution, continue to heat to 87 °C after the addition is completed, and keep the reaction for 1 hour; (3) After the reaction is completed, the reaction system is cooled to 80°C, 15 ml of the second pre-emulsion and 11 g of a 1 wt% potassium persulfate solution are added to the reaction solution, and after the addition is completed, the temperature is raised to 87°C and the temperature is kept for 1 hour. After the reaction is completed, the reaction solution is cooled to room temperature to obtain a modified core-shell acrylic dispersion; (4) According to the metering ratio, 85 parts of the modified core-shell acrylic dispersion, 5 parts of the multifunctional composite filler prepared in Example 1, 0.5 parts of a defoamer, 0.5 parts of a wetting agent, 4 parts of a thickener, 2 parts of a film-forming aid, and 30 parts of deionized water are mixed and dispersed uniformly to obtain a water-based coating. Example 4
[0050] Compared with Example 3, the difference is that an equal amount of the multifunctional composite filler of Example 2 is used to replace the multifunctional composite filler prepared in Example 1, and other conditions are the same as those of Example 3. Example 5
[0051] Compared with Example 3, the difference is that the added amount of the multifunctional composite filler is 6 parts, and the other conditions are the same as those of Example 3.
[0052] Comparative Example 7 Compared with Example 3, the difference is that an equal amount of the filler of Comparative Example 1 is used to replace the multifunctional composite filler prepared in Example 1, and other conditions are the same as those of Example 3.
[0053] Comparative Example 8 Compared with Example 3, the difference is that an equal amount of the filler of Comparative Example 2 is used to replace the multifunctional composite filler prepared in Example 1, and other conditions are the same as those of Example 3.
[0054] Comparative Example 9 Compared with Example 3, the difference is that an equal amount of the filler of Comparative Example 3 is used to replace the multifunctional composite filler prepared in Example 1, and other conditions are the same as those of Example 3.
[0055] Comparative Example 10 Compared with Example 3, the difference is that an equal amount of the filler of Comparative Example 4 is used to replace the multifunctional composite filler prepared in Example 1, and other conditions are the same as those of Example 3.
[0056] Comparative Example 11 Compared with Example 3, the difference is that an equal amount of the filler of Comparative Example 5 is used to replace the multifunctional composite filler prepared in Example 1, and other conditions are the same as those of Example 3.
[0057] Comparative Example 12 Compared with Example 3, the difference is that an equal amount of the filler of Comparative Example 6 is used to replace the multifunctional composite filler prepared in Example 1, and other conditions are the same as those of Example 3.
[0058] Comparative Example 13 Compared with Example 3, the difference is that no multifunctional composite filler is added, and other conditions are the same as those of Example 3.
[0059] Comparative Example 14 Compared with Example 3, the difference is that in step (2), no nano titanium dioxide is added, and the other conditions are the same as those in Example 3.
[0060] Comparative Example 15 Compared with Example 3, the difference is that in step (2), nano titanium dioxide is not added, and in step (4), multifunctional composite filler is not added. Other conditions are the same as those in Example 3.
[0061] The water-based coatings of the above-mentioned Examples 3-5 and Comparative Examples 7-15 were subjected to performance tests, and the test methods and test results are as follows.
[0062] 1. Storage stability test: The coatings of Examples 3-5 and Comparative Examples 7-15 were stored at room temperature for 7 days, and the dispersion of the coatings was observed.
[0063] 2. Antibacterial performance test: The test was conducted in accordance with HG / T3950-2007 standard, using data from Staphylococcus aureus and Escherichia coli after 56 days, and the measured values were taken as the average of 10 tests.
[0064] The coatings of Examples 3-5 and Comparative Examples 7-15 were sprayed on steel plates respectively and cured for 5 days to obtain a coating with a thickness of 80 μm. The coating was tested for its performance: 3. Adhesion test: According to GB / T9286-1998 standard, the test is carried out by cross-cutting method. A grid with a spacing of 1mm is drawn on the surface of the coating, and the peeling is observed after peeling with tape. The rating standard is 0-5, where 0 means no peeling and 5 means the peeling area exceeds 65%.
[0065] 4. Chemical resistance test: The cured coating was placed in a medium including water, acid (10% by mass HCl) and alkali (10% by mass NaOH). After 200 hours, it was taken out and dried with filter paper to observe the bubbling and rusting phenomena.
[0066] 5. Impact resistance test: The test is carried out in accordance with GB / T1732-1993 "Determination of the impact resistance of coatings". The impact test is carried out at different heights using an impact tester. Three points are selected for the impact test on each sample. If one point fails, it is considered a failure. Select a suitable impact height and then carry out the test to obtain the final result.
[0067] 6. Wear resistance test: According to the test method specified in GB 1768-2006 “Paints and varnishes / Determination of abrasion resistance / Rotating rubber grinding wheel method”, the mass loss of the test sample was tested under the test conditions of CS-17 grinding wheel, 1000g / 1000r.
[0068] 7. UV aging performance test: The coatings of the above-mentioned embodiments and comparative examples were prepared into coating films with a thickness of 2 mm, and the coating films were cut into samples of 100 mm×50 mm, placed under a 30 W ultraviolet lamp, 5 cm away from the light source, and irradiated for 240 h. The tensile properties of the samples were tested before and after irradiation. The tensile properties were tested using a universal tensile testing machine at a stretching speed of 2 mm / min.
[0069] 8. Limiting oxygen index test: The ZR-01 intelligent oxygen index tester was used to detect the limiting oxygen index of polypropylene composite materials with flame retardant coating according to GB / T38301-2019.
[0070] The test results are shown in Table 1 and Table 2.
[0071] Table 1
[0072] Table 2
[0073] The test results of Table 1 and Table 2 are analyzed as follows: Compared with the comparative example, the water-based coatings prepared in Examples 3-5 of the present invention are modified by adding a multifunctional composite filler composed of modified calcium aluminum hydrotalcite material, grafted modified graphene / boron nitride material, and functionalized carbon black. The comprehensive properties of the coatings, such as adhesion, antibacterial, chemical resistance, wear resistance, impact resistance, tensile strength, and flame retardancy, are improved to a certain extent, and the coatings have good stability.
[0074] Compared with other comparative examples, the water-based coating of comparative example 15 did not add the multifunctional composite filler, and the nano-titanium oxide modification was not added in the preparation of the modified core-shell acrylic dispersion, and the performance of the coating was the worst.
[0075] Compared with the embodiments, in comparative examples 7-12, the filler in the water-based coating is a single component or a composite of two components, and the comprehensive performance of the coating is not as good as that of the embodiments, which shows that the three components in the functional composite filler of the present invention have a certain synergistic effect.
[0076] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A water-based coating modified with a multifunctional composite filler, characterized in that: The invention comprises, by weight, 80-100 parts of a modified core-shell acrylic dispersion, 5-7 parts of a multifunctional composite filler, 0.5-1 parts of a defoamer, 0.5-1 parts of a wetting agent, 2-5 parts of a thickener, 1-2 parts of a film-forming aid, and 25-35 parts of deionized water; the multifunctional composite filler is a mixture of a modified calcium aluminum hydrotalcite material, a grafted modified graphene / boron nitride material, and functionalized carbon black, and the mass ratio of the modified calcium aluminum hydrotalcite material, the grafted modified graphene / boron nitride material, and the functionalized carbon black is (2-5): (3-8): (10-20); the core of the modified core-shell acrylic dispersion is nano-titanium dioxide, and the outer layer is coated with acrylic resin and fluorine-modified acrylic resin in sequence; The modified calcium aluminum hydrotalcite material is prepared by first inserting sodium dodecylbenzene sulfonate between the calcium aluminum hydrotalcite material layers, and then inserting acrylamide; The grafted modified graphene / boron nitride material is prepared by intercalating graphene and boron nitride and then subjecting them to silanization treatment, and finally grafting and polymerizing methacryloyloxyethyl sulfobetaine as a monomer; The functionalized carbon black is prepared by pre-treating carbon black and then modifying it with beta-cyclodextrin and glycerol phytate ammonium salt. The glycerol phytate ammonium salt is prepared by esterifying glycerol with phytate and then reacting with urea for complexation.
2. The water-based paint modified by a multifunctional composite filler according to claim 1, characterized in that: The preparation method of the modified calcium aluminum hydrotalcite material specifically comprises the following steps: The calcium aluminum hydrotalcite is dispersed in deionized water to obtain a calcium aluminum hydrotalcite dispersion, a sodium dodecylbenzene sulfonate solution is added to the calcium aluminum hydrotalcite dispersion, an acrylamide solution is added after ultrasonic dispersion treatment, and the pH of the solution is adjusted to react. After the reaction is completed, the reaction solution is cooled to room temperature, the reaction solution is filtered, the filtered precipitate is washed, and then dried to obtain a modified calcium aluminum hydrotalcite material.
3. The water-based paint modified by a multifunctional composite filler according to claim 2, characterized in that: The concentrations of the calcium aluminum hydrotalcite dispersion, sodium dodecylbenzene sulfonate solution, and acrylamide solution are 0.05-0.08 g / ml, 0.05-0.06 g / ml, and 0.02-0.05 g / ml, respectively; the mass ratio of the calcium aluminum hydrotalcite dispersion, sodium dodecylbenzene sulfonate solution, and acrylamide solution is 1:1:(0.5-1); The reaction has a pH of 3.5-4.5, a temperature of 80° C., and a reaction time of 3-5 h.
4. The water-based paint modified by a multifunctional composite filler according to claim 1, characterized in that: The preparation method of the grafted modified graphene / boron nitride material comprises the following steps: Graphene and boron nitride are added to anhydrous ethanol in a mass ratio of (2-5):1, and ultrasonically treated at 200-500W for 1-3h, then filtered, and the precipitate is directly added to a methacrylate-3-(trimethoxysilyl)propyl ester solution without drying for immersion activation treatment, then filtered, and the precipitate is washed and directly added to a mixed solution of methacryloyloxyethyl sulfobetaine, a photoinitiator, and N,N-methylenebisacrylamide without drying, stirred and dispersed evenly, and then ultraviolet graft polymerization is carried out, and finally the reaction solution is filtered, the precipitate is washed and dried to obtain a grafted modified graphene / boron nitride composite material.
5. The water-based paint modified by a multifunctional composite filler according to claim 4, characterized in that: The preparation of the grafted modified graphene / boron nitride material includes at least the following features: a: The 3-(trimethoxysilyl)propyl methacrylate solution is prepared by adding 3-(trimethoxysilyl)propyl methacrylate to a mixed solution of methanol and deionized water; the volume ratio of 3-(trimethoxysilyl)propyl methacrylate, methanol and deionized water is 5:(90-95):(3-5); b: The temperature of the immersion activation treatment is room temperature, the time is 20-30 hours, and the mass ratio of the precipitate to 3-(trimethoxysilyl)propyl methacrylate is 1:(0.03-0.05); c: During UV graft polymerization, the photoinitiator is 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone; the mass ratio of the precipitate to methacryloyloxyethyl sulfobetaine is 1:(0.01-0.05); d: In the mixed solution, deionized water is used as the solvent, the concentration of methacryloxyethyl sulfobetaine is 0.1-0.2 g / ml, and the mass ratio of methacryloxyethyl sulfobetaine, N,N-methylenebisacrylamide, and photoinitiator is 5:(0.02-0.03):(0.01-0.05); e: The conditions for UV graft polymerization are: irradiation with a high-pressure mercury lamp with a power of 400 W and a UV wavelength of 365 nm, a radiation distance of 15 cm, and a time of 20-30 min.
6. The water-based paint modified by a multifunctional composite filler according to claim 1, characterized in that: The preparation method of the functionalized carbon black comprises the following steps: Phytic acid and glycerol are added to ethanol to carry out a temperature reaction, and then urea is added to the reaction system to carry out a second temperature reaction. After the reaction is completed, it is cooled to room temperature, β-cyclodextrin and pretreated carbon black are added to the reaction system, ultrasonic treatment is carried out, and finally the reaction solution is filtered, the precipitate is washed and dried to obtain functionalized carbon black.
7. The water-based paint modified by a multifunctional composite filler according to claim 6, characterized in that: The molar ratio of phytic acid, glycerol and urea is (0.02-0.03): (0.09-0.1): (0.1-0.2); and / or the mass ratio of β-cyclodextrin, pretreated carbon black and phytic acid is 2:1:(0.5-1); And / or the temperature of the first heating reaction is 130°C and the time is 2-3h; the temperature of the second heating reaction is 110°C and the time is 2-3h; the temperature of the ultrasonic treatment is room temperature, the power is 200-500W, and the time is 20-50min.
8. A method for preparing a water-based coating modified with a multifunctional composite filler according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) preparing an emulsifier solution, stirring and mixing the first monomer and the emulsifier solution to obtain a first pre-emulsion; Adding the second fluorine-containing monomer into the emulsifier solution and stirring evenly to obtain a second pre-emulsion; (2) Add nano titanium dioxide to the emulsifier solution, stir evenly to obtain a dispersion, add 1 / 3 of the first pre-emulsion to the dispersion, heat it to 80±2°C, add 1 / 3 of the initiator solution, react until blue light appears, add the remaining first pre-emulsion and initiator solution, continue to heat to 87±2°C after the addition is completed, and keep the reaction warm for 0.5-1h; (3) After the reaction is completed, the reaction system is cooled to 80±2°C, and the second pre-emulsion and the initiator solution are added to the reaction solution. After the addition is completed, the temperature is raised to 87±2°C and the temperature is kept to react for 0.5-1h. After the reaction is completed, the reaction solution is cooled to room temperature to obtain a modified core-shell acrylic dispersion; (4) The modified core-shell acrylic dispersion, multifunctional composite filler, defoamer, wetting agent, thickener, film-forming aid and deionized water are mixed and dispersed uniformly according to the measured ratio to obtain a water-based coating.
9. The method for preparing a water-based coating modified with a multifunctional composite filler according to claim 8, characterized in that: In step (1), the first monomer is a mixture of methyl methacrylate, butyl acrylate and acrylic acid. When preparing the first pre-emulsion, the mass ratio of methyl methacrylate, butyl acrylate, acrylic acid and emulsifier is (8-15): (10-15): 3: (0.3-0.5); and / or the fluorine-containing second monomer is a mixture of methyl methacrylate, butyl acrylate, acrylic acid, glycidyl methacrylate, isooctyl acrylate, hydroxyethyl methacrylate, and trifluoroethyl acrylate. When preparing the second pre-emulsion, the mass ratio of methyl methacrylate, butyl acrylate, acrylic acid, glycidyl methacrylate, isooctyl acrylate, hydroxyethyl methacrylate, trifluoroethyl acrylate, and emulsifier is (5-8): (10-12): (1-2): (2-4): (1-1.5): (2-4): (2-3): (0.3-0.5); During the polymerization, the volume ratio of the first pre-emulsion, the second pre-emulsion and the emulsifier solution in the dispersion is 3:3:
10.
10. The method for preparing a water-based coating modified with a multifunctional composite filler according to claim 8, characterized in that: The emulsifier solution is a sodium dodecyl sulfate solution with a concentration of 0.5-1wt%; the initiator solution is a potassium persulfate solution with a concentration of 1wt%; In step (2), the mass ratio of nano titanium dioxide to emulsifier is 5:(1-1.5); The mass ratio of the initiator solution in step (2) to the emulsifier solution in the dispersion is 1:(4-5); The amount of the initiator solution added in step (3) is 0.2-0.3 times the mass of the emulsifier solution in the dispersion.
Citation Information
Patent Citations
Method for preparing hydrotalcite intercalation structure high water-absorbent resin additives
CN101381428A
Flame retardant smoke-suppression type humidity controlling functional coating and preparation method thereof
CN102408791A
Preparation method for long-acting water-based antirust agent for metal
CN106854487A
Ammonium phytate flame retardant, preparation method thereof and flame retardant and toughened polylactic acid material
CN108047494A
Environmentally friendly calcium zinc composite stabilizing agent and preparation method thereof
CN109825008A
Cited By
Low-VOCs (Volatile Organic Compounds) anti-ultraviolet heat-insulating coating composition and performance testing device thereof
CN120464271A
Low vocs uvioresistant heat insulation coating composition and performance testing device thereof
CN120464271B
Anti-ultraviolet acrylic resin coating and preparation method thereof
CN121203479A